Effect of thermal condition on isothermal-pressing joined strength of silanized Al alloy/carbon fiber-reinforced polyamide-6 - Weihao Li; Peihao Geng; Qian Wang; Ninshu Ma; Shuaijie Zhao; Chuantong Chen (Journal of Materials Research and Technology, 2023)
Carbon fiber-reinforced thermoplastics (CFRTPs) and lightweight metals are widely used in multi-material structures owing to their high strength and excellent corrosion resistance, thus stimulating research on various heat-assisted techniques to join them. Currently, the isothermal-pressing process has been developed to realize sound interface joining between CFRTP and Al alloy under relatively uniform thermal conditions. However, a quantitative investigation of the interaction between thermal conditions, chemistry reactions, and joining strength is still lacking. This current investigation analyzed chemical reaction state and resultant bonded strength of isothermal-pressing joined interface of silanized 5052 Al alloy and carbon fiber-reinforced polyamide-6 (CF/PA6) under various thermal conditions. X-ray photoelectron spectroscopy and Raman scattering analysis showed the increasing consumption of epoxy groups on silanized 5052 Al alloy side with the increase in joining temperature and residence time. This suggested higher temperatures and sufficient high-temperature duration times could efficiently promote the interface chemical reaction, increasing interface bonding strength. As the joining temperature or residence time increased, the fracture location gradually shifted from the silane coupling layer/re-solidified resin interface to the re-solidified resin close to interface, and even it directly passed through CF/PA6 along the thickness direction. Under the current adopted conditions, a critical high-temperature duration time of ∼6.0 s at least was recommended by optimizing the joining time to achieve high-strength joining between 5052 Al alloy and CF/PA6. The findings will guide optimizing the joining conditions in heat-assisted joining processes of Al/CFRTP hybrid structures.